Comparison of platelet‐rich fibrin and cellulose in palatal wounds after graft harvesting. Issue 4 (27th September 2019) - Patarapongsanti, Arada; Bandhaya, Panwadee; Sirinirund, Benyapha; Khongkhunthian, Sakornratana; Khongkhunthian, Pathawee
Abstract: Aim: The aim of the present study was to compare patient morbidity and healing outcomes of free gingival graft (FGG) harvesting at palatal donor sites and after using platelet‐rich fibrin (PRF) and oxidized regenerated cellulose (ORC). FGG harvesting leaves open palatal wounds, which heal by secondary intention. Patients might experience discomfort or pain during the first 2 weeks of healing. Methods: Eighteen participants requiring two FGG were recruited. The test and control sites were covered with PRF membrane and ORC. The complete epithelialization of the palatal wound, the percentage of wound healing, and postoperative pain were evaluated, 1, 3, and 7 days and 2, 3, and 4 weeks after surgery. Results: Similar wound size reduction at 1 week (test: 36.87%, control: 38.78%) was found. At 2 weeks, the majority of the test group (88.89%) showed complete epithelialization, whereas 66.67% of the control group had complete epithelialization ( P  =   .228). Pain was more prevalent in the control group (27.77%) than in the test group (11.1%) on day 1. None of the participants reported any pain or discomfort at the test sites on day 3. Conclusions: PRF seems to reduce patient morbidity, but there is no difference in palatal wound healing ( P  > .05).